Implications of Neuroimmunity in Alzheimer’s Disease: A Review - Katriel Lee (Impulse: The Premier Undergraduate Neuroscience Journal, 2017)
AD is characterized cognitively by memory, problem-solving, and language difficulties. It is estimated that 5.4 million Americans currently have Alzheimer’s disease (AD). The cognitive difficulties in AD are reflected in the brain through the accumulation of amyloid-β (Aβ) in cerebral amyloid angiopathy (CAA), neurofibrillary tau tangles, neuronal tissue atrophy, and neuroinflammation, but the exact cause of AD is still in question. However, evidence suggests that differences in neuroimmune function—the central nervous system’s ability to resist disease—may play a role in the development and progression of AD. This paper largely relates neuroimmune changes to the amyloid hypothesis of AD. This approach relates AD to Aβ production and clearance, and therefore, targets Aβ for treatment uses. A thorough literature search revealed evidence that the blood-brain barrier (BBB), glial cell mediation and effects on neuroinflammation, and cerebrospinal fluid (CSF) and interstitial fluid (ISF) drainage systems are changed in AD. These changes seem to be detrimental for the AD brain and Aβ accumulation. Future research should be conducted regarding characterization of the lymphatic system in the human dura, the balance of helpful and harmful effects of activated microglia, the driving forces of paravascular CSF-ISF exchange, the effects of sleep on neuroimmunity, and genetic risk factors for neuroimmune dysfunction.